ISODUS Application Design for Web-Based School Academic Administration Operational System Information. Case Study: Al Alaq Islamic Middle School - Jalaludin; Amirudin; Achmad Faruq Ali; Susy Rosyida (MBI, 2024)
The aim of the research is to support technological independence in educational units in processing data archives and general finances at the Al Alaq Islamic Middle School and what are the obstacles encountered in implementing such a system. In addition, the authors hope that readers can understand the use of this academic administration information system application known as ISODUS. During the research, the authors found that the Al Alaq Islamic Middle School did not have a computerized academic administrative and financial data processing system so that it could help find information quickly and effectively. This is due to the lack of human resources who know about information systems. After conducting some research, the authors conclude that Al Alaq Islamic Middle School requires a computerized system so that it can assist teachers in making administration. The author tries to create an Academic Administration system using the PHP programming language.